Cartografia da educação no Estado de São Paulo: 1850 - 1967 - Bonfante, Felipe Janini (Universidade Estadual Paulista (Unesp), 2020)
Durante o período de 1851 a 1967 a educação pública paulista passou por diversas reorganizações consolidadas a partir de leis e decretos, cada qual a reordenando espacialmente sob forma de regiões administrativas e sob diversas nomenclaturas. Iniciando em 1851 com a criação dos Distritos de Instrução Pública, seguindo da criação das Zonas de Inspeção, Distritos Escolares e posteriormente as Zonas Escolares e Delegacias de Ensino, cada qual regido por legislação própria. Desta forma, a educação teve uma constante reorganização espacial no território paulista. A cada etapa do longo processo de descentralização das políticas públicas, novas regionalizações para a educação no estado foram definidas afetando diretamente a forma de administração do ensino. Através de pesquisa documental e produção cartográfica delineamos o processo acima exposto. Demonstramos que a efemeridade inicial da regionalização a partir da metade do século XIX tornou-se mais consolidada com a evolução da racionalização burocrática e a evolução territorial paulista. A regionalização da educação seguiu seus próprios ordenamentos regionais, acompanhando o movimento pendular entre descentralização e centralização do poder estatal até 1967, quando foi submetida à regionalização administrativa do estado.

During the period from 1851 to 1967, the Public Education from São Paulo passed through reorganizations consolidated by laws and decretes, each one reordering it spatially under shape of administrative regions under miscellaneous nomenclatures. Initiating in 1851 with the creation of Public Instruction Districts, following the creation of Inspection Zones, School Districts and posteriorly the School Zones and Teaching Stations, each responding by it's own legislation. Thus the education had a constant spatial reorganization in São Paulo territory. Each step over the proccess of descentralization of new public politics, new regionalizations for the education in the state has been defined, directly affecting the shape of the teaching administration. Through files research and cartographic production, we trace the proccess exposed above. We will show that the inicial illness of the regionalization starting in half of XIX century became more consolidated with the evolution of burocratic racionalization and territorial state evolution. The education's regionalization followed his own orders untill 1967, when it was submitted to administrative regionalization of the state, showing pendular movement between descentralization and centralization of the power.ddle of the 19th century has become more consolidated with the evolution of bureaucratic rationalization and the territorial evolution of São Paulo. The regionalization of education followed its own regional order, following the pendular movement between decentralization and centralization of state power until 1967, when it was subjected to administrative regionalization of the state.
Cartography of education in the State of São Paulo: 1850 - 1967
Keywords: Regionalização; Ensino; Legislação; Cartografia